2010
DOI: 10.1088/0029-5515/50/12/125004
|View full text |Cite
|
Sign up to set email alerts
|

The ecton mechanism of unipolar arcing in magnetic confinement fusion devices

Abstract: It has been shown that the source of current and erosion plasma in a unipolar arc is explosive electron emission, which occurs as ejection of individual portions of electrons named ectons. This phenomenon is responsible for the numerous microcraters left by unipolar arcs on metal surfaces. An arc of this type is self-sustained due to the interaction of the erosion plasma with the electrode surface. The duration of an arc is determined by the conditions of its initiation: the higher the arc current, and hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 34 publications
0
26
0
1
Order By: Relevance
“…Next, the effects of the fuzzy layer thickness on the erosion processes were analysed. For spherically symmetric destruction of the surface, the radius of the crater formed due to Joule heating during the operation of a cathode spot cell is determined by the formula rex=icfalse/2πt/htrue‾1false/4, where i c is the cell current . For sufficiently thick fuzzy layers, assuming that the cathode destruction rate dr ex / dt is equal to the velocity of the heat wave d ( αt ) 1/2 / dt , the radius of the crater formed due to Joule heating rexi=icfalse/()4παtrueh can be estimated in this case, yielding r exi ≈ i c · 2.2 µm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the effects of the fuzzy layer thickness on the erosion processes were analysed. For spherically symmetric destruction of the surface, the radius of the crater formed due to Joule heating during the operation of a cathode spot cell is determined by the formula rex=icfalse/2πt/htrue‾1false/4, where i c is the cell current . For sufficiently thick fuzzy layers, assuming that the cathode destruction rate dr ex / dt is equal to the velocity of the heat wave d ( αt ) 1/2 / dt , the radius of the crater formed due to Joule heating rexi=icfalse/()4παtrueh can be estimated in this case, yielding r exi ≈ i c · 2.2 µm.…”
Section: Discussionmentioning
confidence: 99%
“…From a theoretical point of view, the arc ignition present on the fuzzy W surfaces under fusion‐relevant conditions has been explained by the ecton mechanism, which accounts for a cathode spot as an individual explosive electron emission cell, referred to as an ecton . The motion and erosion properties that depend on the fuzzy layer thickness were discussed using that theoretical basis .…”
Section: Introductionmentioning
confidence: 99%
“…The time cutoff is derived by the observation of smoothing of a surface, rather than crater formation, when the discharge pulse duration is less than 5 ns [94]. The lower limit of the length scale is found from the smallest macroparticles and crater sizes [118,119]. The ignition of cathode spots has much in common with high voltage electrical breakdown [92,120].…”
Section: Cathodic Arc Plasma Production With Emphasis On Pulsed Arcsmentioning
confidence: 99%
“…The experimental results exhibited interesting and essential characteristics in grouping feature of arc spot cells. Earlier, we attempted to interpret the experimental results by considering the processes occurring during the operation of an individual cell of the cathode spot of a vacuum arc 19,20 in the context of the explosive-emission center (ecton) model of a cathode spot. 21 It has been shown that as a spot cell moves to a thick nanostructured layer, the size of the crater it leaves increases and its velocity decreases.…”
Section: Introductionmentioning
confidence: 99%